Pathways in the periphery: tourism to indigenous communities in Panamá (2022)
eng: Objective. In this era of neoliberal economic policies, tourism offers developing nations a rare opportunity for a source of economic growth that can substantially benefit the poorest of the poor: indigenous peoples. Very little is known, however, about the circumstances that allow visitors' dollars to assist indigenous communities most effectively and those that can make tourists a destructive presence. Methods. The paper analyzes, in comparative perspective, tourism to two indigenous nations in Panama, the Kuna and the Emberá/Wounaan. The central data upon which the paper is based consist of forty-two interviews with Indians, conducted at twelve different tourist locations in Panama; sixteen interviews with all ten firms offering tours to indigenous communities in 1996-97; and interviews and informal discussions with government officials, biologists, members of nongovernmental environmental organizations, and academic specialists in indigenous affairs. The majority of the interviews were conducted from June to December 1996. Other data include published and nonpublished materials from the Kuna and Emberá/Wounaan Congresses. Translations from the Spanish are the authors'. Results. The paper finds that where indigenous culture is relatively strong (i. e., less influenced by non-Indian society), tourism tends to cause its decay; where it is relatively weak, tourism can give incentives for its regeneration. Conclusions. While there are some unavoidable negative effects associated with tourism, indigenous communities can ameliorate some problems by formulating a clear plan and educating the members of their communities as to its contents.